Leadership Changes in Primary Schools of Bangladesh Due to the COVID-19 Pandemic (Teacher’s World: Journal of Education and Research, 2024)
In the COVID-19 pandemic, schools across the world, including those in Bangladesh, have experienced significant changes in their leadership dynamics. This paper presents a qualitative case study that displays the leadership transformations in primary schools in Bangladesh due to the pandemic. Utilizing a convenience sampling strategy, two government primary schools were selected as cases, and their head teachers along with all class teachers were chosen as participants. Through in-depth interviews and focus group discussions, data were collected and analyzed thematically. The findings reveal distinct differences in leadership before, amid, and after the pandemic, highlighting various aspects of change. These include the leadership shifts from classroom to online teaching, the transition of administrative meetings to virtual platforms, navigating co-curricular activities from in-person to online settings, fostering guardian involvement for student well-being, reconfiguring textbook distribution fest to house-to-house methods, leading school feeding programs involving NGOs, and more. Additionally, the research highlights teachers’ technological and peer-based training initiatives and the transition from exam hall-based assessments to assignment-based assessment systems. Furthermore, the study touches on the challenges of dealing with student dropouts. These findings contribute to a deeper understanding of the critical role of leadership in adapting school leaders to unforeseen challenges and provide valuable insights for educational institutions.Teacher’s World: Journal of Education and Research, 49 (1),19-32